The impact of environmentally balanced agricultural systems on changes in the agrophysical state of typical chernozem soil and the energy management of sunflower cultivation - Butenko, Yevheniia; Бутенко, Євгенія; Rudska, Nina; Рудська, Ніна; Kovalenko, Nataliia; Коваленко, Наталія; Hotvianska, Anna; Готвянська, Анна Сергіївна; Horshchar, Vladyslav; Горщар, Владислав Іванович; Tkachenko, Roman; Ткаченко, Роман; et al. (Politechnika Lubelska – Lublin University of Technology, 2025)
The relevance of the studies lies in developing methods for primary tillage of soil under sunflower that significantly affect agrophysical indicators. This task acquires special importance under conditions of unstable and insufficient moisture. It is expected to improve the agrophysical properties that would impact the soil's moisture balance and control of crop weeds, which would subsequently allow obtaining high yields. Therefore, the need to develop such methods of primary tillage under row crops, primarily under sunflower, becomes urgent. The study took place in the Left-Bank Forest-Steppe zone of Ukraine (Sumy region), utilizing typical low-humus chernozem soil throughout the years 2023–2024. It was found that the largest reserves of productive moisture in the arable horizon at the time of sunflower sowing with plowing at 20–22 cm were 16.9 mm, and the smallest at no-till disc cultivation were 16.4 mm. At the time of harvest, the moisture reserves significantly reduced to a critical level, namely to 0.6–1.0 mm in the arable horizon and to 24.0–25.8 mm in the meter horizon. During the sunflower's germination period, the density of the arable layer soil remained within the optimal range across all soil treatment methods, with values for plowing ranging from 1.14 to 1.24 g/cm3, deep loosening – 1.17–1.26 g/cm3, no-till treatment with a heavy cultivator at 12–14 cm – 1.22–1.28 g/cm3, and disc cultivation at the same depth – 1.20–1.27 g/cm3. The density of the arable horizon under sunflower increased more significantly at plowing than at no-till treatments from plant emergence to harvest. The yield of sunflower seeds in the variant with plowing was the highest – 3.28 t ha-1. Soil treatments without turning the soil, both deep at 35–40 cm and shallow at 12–14 cm, led to a significant decrease in sunflower seed yield by 0.40–0.71 t ha-1 at LSD05 – 0.04 t ha-1. The coefficient of energy efficiency was lowest at plowing under sunflower – 2.6. As the energy intensity of the sunflower yield decreased at no-till soil treatments without turning the soil, it increased to 3.0–3.3. Актуальність досліджень полягає в розробці методів основного обробітку ґрунту під соняшником, які суттєво впливають на агрофізичні показники. Це завдання набуває особливої важливості в умовах нестабільного та недостатнього зволоження. Очікується покращення агрофізичних властивостей, що вплине на баланс вологи ґрунту та боротьбу з бур'янами посівів, що згодом дозволить отримувати високі врожаї. Тому необхідність розробки таких методів основного обробітку ґрунту під просапні культури, насамперед під соняшник, стає актуальною. Дослідження проводилося в Лівобережному Лісостепу України (Сумська область) на типовому малогумусному чорноземі протягом 2023–2024 років. Встановлено, що найбільші запаси продуктивної вологи в орному горизонті на момент сівби соняшнику з оранкою на 20–22 см становили 16,9 мм, а найменші при безоранковому дисковому обробітку – 16,4 мм. На момент збору врожаю запаси вологи значно знизилися до критичного рівня, а саме до 0,6–1,0 мм в орному горизонті та до 24,0–25,8 мм в метровому горизонті. Протягом періоду сходів соняшнику щільність орного шару ґрунту залишалася в оптимальному діапазоні за всіх способів обробітку ґрунту, зі значеннями за оранки від 1,14 до 1,24 г/см3, глибокого розпушування – 1,17–1,26 г/см3, безоранкового обробітку важким культиватором на 12–14 см – 1,22–1,28 г/см3 та дискового обробітку на ту саму глибину – 1,20–1,27 г/см3. Щільність орного горизонту під соняшником суттєвіше зростала за оранки, ніж за безоранкового обробітку від сходів рослин до збору врожаю. Урожайність насіння соняшнику у варіанті з оранкою була найвищою – 3,28 т га-1. Обробки ґрунту без перевертання, як глибокі на 35–40 см, так і неглибокі на 12–14 см, призвели до значного зниження врожайності насіння соняшнику на 0,40–0,71 т га-1 при LSD05 – 0,04 т га-1. Коефіцієнт енергетичної ефективності був найнижчим за оранки під соняшник – 2,6. Зі зниженням енергоємності врожайності соняшнику за безоранкових обробок ґрунту без перевертання вона збільшилася до 3,0–3,3.
Вплив екологічно збалансованих сільськогосподарських систем на зміни агрофізичного стану типового чорнозему та енергетичний менеджмент вирощування соняшнику
Keywords: Management; управління; soil density; щільність ґрунту; biological activity; біологічна активність; crop structure; структура культури; water-physical properties; водно-фізичні властивості; productive moisture; продуктивна волога; energy assessment; енергетична оцінка; bulk soil mass; об'ємна маса ґрунту